Nurturing Peer Review Proficiency in the Curriculum for Early Career Medical Researchers: Fostering Academic Connectivity - Amit Kumar; Manjunath P. Puranik (Wolters Kluwer Medknow Publications, 2024)
Peer review is being criticized for its sluggishness and review quality. Swiftly identifying available reviewers and cultivating a pool of specialized experts is crucial to avoid delays and ensure a seamless peer review process. A promising strategy to enhance the quality of peer reviewers is to encourage and facilitate early career researchers (ECRs) to engage in co-reviewing with their mentors as part of their curriculum training. In addition, it holds significant potential to bridge gaps in research quality and discourage unethical ghostwriting of peer review reports. Encouraging co-reviewing practices in medical, dental, nursing, and other professional institutions will foster the development of critical skills, research awareness, mentorship, and collaborative abilities among ECRs. This paper proposes learning peer review modules in a two-step model, i.e., foundational learning and practical learning. Emphasizing peer review within the curriculum can be a significant and transformative step.